2016
DOI: 10.22323/2.15050202
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting disaster: an analysis of online discourse about nuclear power in the wake of the Fukushima Daiichi nuclear accident

Abstract: Of all the online information tools that the public relies on to collect information and share opinions about scientific and environmental issues, Twitter presents a unique venue to assess the spontaneous and genuine opinions of networked publics, including those about a focusing event like the Fukushima Daiichi nuclear accident following the 2011 Tohoku earthquake and tsunami. Using computational linguistic algorithms, this study analyzes a census of English-language tweets about nuclear power before, during,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
21
0
3
Order By: Relevance
“…Despite the popularity and heavy use of social media and digital born media organizations, there is a clear dearth of research that analyses online discourses about nuclear energy. Currently, there are only two empirical works which have examined public discourse about the Fukushima accident on Twitter (Binder, 2012;Li et al, 2016), and one study evaluating nuclear energy-related tweets from the computational science perspective (Satapathy, Chaturvedi, Cambria, Ho, & Na, 2017). This is in stark contrast to the substantial number of studies that have focused on traditional content analysis of news coverage of nuclear energy and survey-based public opinion studies (e.g.…”
Section: Challenges and Research Gaps In Extant Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the popularity and heavy use of social media and digital born media organizations, there is a clear dearth of research that analyses online discourses about nuclear energy. Currently, there are only two empirical works which have examined public discourse about the Fukushima accident on Twitter (Binder, 2012;Li et al, 2016), and one study evaluating nuclear energy-related tweets from the computational science perspective (Satapathy, Chaturvedi, Cambria, Ho, & Na, 2017). This is in stark contrast to the substantial number of studies that have focused on traditional content analysis of news coverage of nuclear energy and survey-based public opinion studies (e.g.…”
Section: Challenges and Research Gaps In Extant Studiesmentioning
confidence: 99%
“…The debates over nuclear energy are further compounded by arguments over other potential benefits of nuclear energy such as reliable energy production, economic competitiveness and stable electricity prices, and the potential adverse effects of nuclear energy such as the possible proliferation of nuclear weapons and the high upfront costs of nuclear power plants (IAEA, 2014). In the aftermath of the 2011 Fukushima-Daiichi nuclear incident in Japan, many nations such as Germany, Belgium, and Switzerland decided to phase out nuclear power, but nations such as China, India, Finland, the UK, and the US are planning or already building new nuclear energy plants Li et al, 2016). For example, analysis of news media coverage in the aftermath of these nuclear accidents showed that the low carbon emission benefit of nuclear energy in mitigating climate change was greatly deemphasized in the media, while the potential threat of ionizing radiation from nuclear power plants to human health and the environment were given the heavy spotlight (Friedman, 2011;Kristiansen, 2017).…”
mentioning
confidence: 99%
“…Specifically, the online discourse has a greater impact on issues related to nuclear energy than the offline discourse does because many individuals construct such a discourse through participation in discussions and dissemination of information in the virtual space, rather than in real life. Li et al [1] showed that, after the Fukushima nuclear disaster, although the public attitude toward nuclear energy changed from a negative to a neutral one over time, the emotions expressed on Twitter became negative. Anderson et al [2] reported that the public receives information on science and technology, including nuclear energy, mainly from the internet, and through social media (particularly through tweets, blogs, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Our methodological approach has recently been successfully used to identify changes in the sentiment of tweets surrounding the Fukushima Daiichi nuclear accident (Li et al, 2016). However, in contrast to Li et al 2016, we rely on a widely-available open-source machine learning algorithm; as a result, we are able to report validation metrics such as classification accuracy, and also offer the potential for replication and extension of our work without the need to rely on proprietary software tools.…”
Section: Methodsmentioning
confidence: 99%